ARE M-CHOLINOCEPTORS OF GUINEA-PIG GALLBLADDER SMOOTH-MUSCLE OF M4 SUBTYPE - ONAT, FİLİZ; ALİCAN, YAŞAR İNCİ (KARGER, 1993)
The antagonism of carbachol-induced contractions of guinea pig gallbladder smooth muscle strips via selective antagonists, methoctramine, HHSiD, pf-HHSiD and DABDMA has been investigated in order to find out the m-cholinoceptor subtype(s) of gallbladder smooth muscle. All m-cholinoceptor antagonists examined, displaced the concentration-response curves to the right parallel in a concentration-dependent manner without affecting the maximum response. Schild analysis of data was consistent with competitive antagonism. -log K(B) values of the antagonists were 7.37 for HHSiD, 7.53 for pf-HHSiD, 6.58 for DABDMA and 7.60 for methoctramine. These results, together with the high affinity of pirenzepine and low affinities of 4-DAMP and AF-DX 116, indicate that the m-cholinoceptors of the guinea pig gallbladder which mediate cholinergic contractions are not of m1-, m2- and m3-subtypes but seem likely to be of m4-subtype.
Keywords: GALLBLADDER; M-CHOLINOCEPTORS; MUSCARINIC RECEPTOR SUBTYPES; HEXAHYDRO-SILA-DIFENIDOL; SELECTIVE ANTAGONISTS; ACETYLENIC ANALOGS; BINDING; AFFINITY; ILEUM; IDENTIFICATION; ENANTIOMERS; INHIBITION